Perancangan Desain 3D Untuk Media Promosi Rumah Menggunakan Blender - Rivaldo, Fabian Effo; hendra, marcos (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2025)
This study utilizes Blender to design 3D exterior house models as a more effective promotionaltool. Using the Multimedia Development Life Cycle (MDLC) method, the process includes concept, design,material collection, production, testing, and distribution stages. Compared to conventional promotionalmethods, 3D visualization offers a more realistic experience, enabling potential buyers to deeplyunderstand the layout and architectural details of a house. Based on a survey of 30 respondents, 92%found the 3D design appealing, detailed, and suitable for promotion. Blender has proven to be anexcellent tool for creating realistic models with high-quality texture support. The study reveals that 3Dvisualization not only enhances the appeal of property promotion but also accelerates the decisionmaking process and optimizes marketing strategies. To provide a more immersive experience,developing interactive features such as virtual tours is highly recommended.